Perancangan Aplikasi Biografi Tokoh Penerima Penghargaan Nobel Dengan Menerapkan Algoritma Horspool Boyer Moore - Damayanti Br Cibro (STMIK Budi Darma, 2021)
The Nobel Prize recipient is very important to know because it makes it easier for the public to see a list of several figures and even the information presented because this award is considered the highest award, while a biography can be said to be a story or information about the life of a figure who has received the highest award so that the public can Know about the character who received the Nobel Prize. String matching uses the Horspool Boyer Moore algorithm to match the pattern to be searched, so that the match in the pattern selection can be seen. It is hoped that Boyer Moore's Horspool Algorithm can complete the match in the search for the award recipient. So that it can help the public in the search for figures who receive the Nobel Prize.